Association of central arterial stiffness with the presence and severity of diabetic retinopathy in Asians with type 2 diabetes. (November 2019) - Zhang, Xiao; Lim, Su Chi; Tavintharan, Subramaniam; Yeoh, Lee Ying; Sum, Chee Fang; Ang, Keven; Yeo, Darren; Low, Serena; Kumari, Neelam
Objective: Arterial stiffness has been associated with diabetic retinopathy; however, the information is limited in Asians. We aim to examine the association of central arterial stiffness with the presence and severity of diabetic retinopathy in type 2 diabetes mellitus patients in Singapore. Methods: Arterial stiffness was estimated by carotid-femoral pulse wave velocity and augmentation index using applanation tonometry method. Digital colour fundus photographs from 1, 203 patients were assessed for diabetic retinopathy. Diabetic retinopathy severity was categorized into non-proliferative diabetic retinopathy and proliferative diabetic retinopathy. Logistic regression model was used to evaluate the associations of diabetic retinopathy with pulse wave velocity and augmentation index. Results: Diabetic retinopathy was diagnosed in 391 (32.5%) patients, including 271 non-proliferative diabetic retinopathy and 108 proliferative diabetic retinopathy. Diabetic retinopathy have higher pulse wave velocity (11.2 ± 3.3 vs 9.5 ± 2.6 m/s, p < 0.001) and augmentation index (28.4 ± 9.4 vs 26.1 ± 10.6%, p < 0.001) than non-diabetic retinopathy. After multivariable adjustment, pulse wave velocity [odds ratio = 1.11 (95% confidence interval = 1.05–1.17), p < 0.001] and augmentation index [odds ratio = 1.03 (95% confidence interval = 1.01–1.04), p = 0.009] was associated with diabetic retinopathy. In severity analyses, pulse wave velocity was associated with non-proliferative diabetic retinopathy [odds ratio = 1.10 (95% confidence interval = 1.03–1.17), p = 0.002] and proliferative diabetic retinopathy [odds ratio = 1.15 (95% confidence interval = 1.06–1.25), p = 0.001] ( p -trend < 0.001). Augmentation index showed significant associations with non-proliferative diabetic retinopathy [odds ratio = 1.02 (95% confidence interval = 1.01–1.04), p = 0.008], but not with proliferative diabetic retinopathy [odds ratio = 1.01 (95% confidence interval = 0.98–1.04), p = 0.36] ( p -trend = 0.03). Conclusion: Central arterial stiffness was associated with the presence and severity of diabetic retinopathy in type 2 diabetes mellitus patients, suggesting its etiologic implication in diabetic retinopathy.